Increasing Public Confidence In Accessing Public Safety Center-119 Services Through First Aid Training - Sunarto Sunarto; Addi Mardi Harnanto ((JKG) Jurnal Keperawatan Global, 2021)
Background: Emergency conditions in Indonesia can be caused by the vulnerability of disasters, accidents and diseases that threaten life or cause disability in humans. Emergency conditions require immediate assistance to prevent death and disability. The community as the first helper holds a very important key to the safety of individuals who are experiencing emergency conditions. Not all people are familiar with the PSC-119 service. The results of the preliminary study also showed that most of the respondents expressed lack of confidence because they had never received any socialization or training on how to provide first aid. Methods: a form of experimental research with a pretest-posttest model, with intervention towards respondents related to actions in first aid training. Respondents in this study were 217 special lay people. The sampling technique in this study was random sampling by distributing invitations to special lay people in the city of Surakarta, consisting of members of the Voluntary Corps, health cadres and Linmas Kelurahan at Surakarta City. The data analysis technique used a t test Results: There was an increase in the value between the pretest and posttest of 12.2 and the result of different test (t test) shows the value of Sig. (2-tailed) is 0.00. Conclusion: There was an increase in community confidence in accessing PSC-119 services after first aid training was carried out for victims with significant emergency conditions.